Program Pengembangan Kewirausahaan Jaranan Laksamana Manggala Tumpang (Kini Menjadi Laksana Manggala) - E. Wara Suprihatin; Sumarwahyudi Sumarwahyudi; Robby Hidajat; Yunanto Adi Prasetyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The Jaranan Laksamana Manggala group, now renamed Laksana Manggala (LM), is a traditional arts group that has grown in the Tumpang area, Malang Regency. Comprised of young members who are passionate about preserving karawitan and jaranan, LM faces increasing challenges as the number of similar groups in the region continues to rise. To remain relevant and competitive, LM is required to be more innovative and creative in both artistic expression and organizational development. This community service program aims to strengthen entrepreneurship through capacity development. The focus includes improving members’ technical skills as dancers and musicians, while also providing training in producing jaranan-themed souvenirs such as Tumpang key chains that offer alternative income opportunities. The program applied a participatory approach through entrepreneurship workshops, group management mentoring, and the use of digital technology for promotion and performance documentation.